Efektivitas Fitoremediasi Pada Air Tanah Tercemar Logam Berat Kadmium di Sekitar Tempat Pembuangan Akhir Talang Gulo Provinsi Jambi - Shally Yanova; Gusri, Lailal (LPPM Universitas Muhammadiyah Riau, 2025)
The Talang Gulo landfill site in Jambi City does not yet receive clean water services from PDAM, so the community uses dug wells to get water needs. The aim of this research is to analyze the heavy metal content in the well water of residents around the Talang Gulo TPA and determine the effectiveness of using water hyacinth plants (Eichhornia crassipes) in reducing the heavy metal Cadmium (Cd) content in the well water of residents around the Talang Gulo TPA. This research is experimental research and analysis of heavy metal concentrations using Atomic Absorption Spectrophotometry (AAS). Based on the research results, the metal concentrations of Cd, Fe, Cr and Cu in residents' well water were respectively 0.054 mg/L; 1.023 mg/L; 0.062 mg/L; and 0.509 mg/L. The level of contamination/pollution of Cd metal is in the highly polluted category, the highest compared to Fe, Cr and Cu metals. After phytoremediation was carried out using water hyacinth plants for 7, 14, 21 and 28 days, the highest level of effectiveness of water hyacinth plants in reducing Cd metal was obtained on the 21st day, namely 93.61%. So, it can be concluded that water hyacinth plants are very effective in reducing the concentration of Cd metal in well water.